2014
DOI: 10.1007/978-3-319-04981-6_41
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Delayed Cerebral Ischemia (DCI) in Subarachnoid Haemorrhage Applying Near-Infrared Spectroscopy: Elimination of the Extracerebral Signal by Transcutaneous and Intraparenchymatous Measurements in Parallel

Abstract: Background: Detection of delayed cerebral ischemia (DCI) in high-grade subarachnoid haemorrhage (SAH) is an unsolved issue. Conventional near-infrared spectroscopy (NIRS) with optodes applied over the skin is controversial because the NIRS signal is contaminated by extracerebral tissue. The objective is to quantify and subtract the contribution from extracerebral tissue from the signal by using measurements in parallel with a NIRS brain tissue probe and conventional NIRS.Methods: In a patient with high-grade S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…cardiac and vascular surgeries) [Maldonado et al ; Kato et al ], the neurosurgical critical care unit (ex. monitoring of seizures or vasospasm) [Yokose et al, ; Keller et al, ; Seule et al, ; Tanaka et al, ] and rehabilitation centers (ex. study of brain plasticity after injury) [Strangman et al, ; Arenth et al, ; Mihara et al, ; Yoshino et al, ; Khan et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…cardiac and vascular surgeries) [Maldonado et al ; Kato et al ], the neurosurgical critical care unit (ex. monitoring of seizures or vasospasm) [Yokose et al, ; Keller et al, ; Seule et al, ; Tanaka et al, ] and rehabilitation centers (ex. study of brain plasticity after injury) [Strangman et al, ; Arenth et al, ; Mihara et al, ; Yoshino et al, ; Khan et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Ecological and long-term recordings of electrical and hemodynamic brain activity together with the evaluation of neurovascular coupling could allow diagnosis and monitoring of acute and chronic diseases that influence brain status and cerebrovascular health (e.g., epilepsy, stroke, vascular dementia, Alzheimer's Disease) [8,[64][65][66]. Such a neuroimaging tool can also be employed during intensive care and surgery [67][68][69][70][71][72]. Furthermore, the technology may be essential in rehabilitation protocols for studying brain plasticity and for implementing neurofeedback protocols based on brain computer interface approaches [73,74].…”
Section: Discussionmentioning
confidence: 99%
“…However, one study showed that an early exposure to hyperoxia in the first few hours of medical care was more harmful than delayed exposure [20]. Furthermore, we were not able to analyze hyperoxia by other techniques such as interstitial brain tissue oxygenation by PbtO 2 probe or by Near Infrared Spectroscopy (NIRS), instead of PaO 2 levels [21][22][23].…”
Section: Limitationsmentioning
confidence: 93%